Pemaknaan Generasi Sandwich Dalam Perspektif Generasi Z (Studi Fenomenologi pada Generasi Z di Kabupaten Kuningan) - Annisa, Nur; Nursanti, Siti; Ramdhani, Muhamad (CV. ITTC INDONESIA, 2024)
The sandwich generation is a group of individuals who are caught between two responsibilities, namely taking care of the upper generation (parents) and the lower generation (younger siblings). This phenomenon is increasingly relevant among generation Z who are entering their productive age by facing financial and emotional challenges in managing family responsibilities. The aim of this research is to explain how generation Z in Kuningan Regency interprets and understands their role as part of the sandwich generation. The research method uses a qualitative method with a phenomenological approach to find information about participants' subjective experiences by conducting in-depth interviews to collect data. The results of this research show that generation Z who are the sandwich generation have different meanings such as family responsibilities, social pressure, disaster and a gift from God to repay their parents' services. This research also found that factors that influence it include the economic, cultural and social conditions of society. It is hoped that this research will provide new insight into the dynamics of the sandwich generation in Indonesia, especially among generation Z, and help identify relevant interventions to support them in carrying out this role.